Citoyens de deuxième classe ? Perceptions de la santé et du système de soins chez les francophones du nord-est de l’Ontario - Bernier, Christiane (Francophonies d'Amérique, 2009)
Cette enquête a pour objectif d’analyser les représentations que les francophones vivant en situation minoritaire ont de leur santé et de celle de leur communauté, de même que leurs perceptions des systèmes de soins auxquels ils ont accès, particulièrement lorsqu’ils vivent dans des régions rurales ou éloignées. De type qualitatif, l’enquête a été réalisée dans le nord-est de l’Ontario auprès de 32 francophones provenant de dix villes différentes. Les résultats montrent que le mépris de la langue minoritaire, le manque de services et de considération pour les francophones ainsi que le faible intérêt accordé par le gouvernement aux usagers des régions éloignées sont les pivots autour desquels se construisent l’insécurité et les désillusions par rapport au système de santé de la province.

Barrières linguistiques dans l'accès aux soins de santé - Bowen, Sarah (Santé Canada, 2001)

Language barriers in access to health care - Bowen, Sarah (Health Canada, 2001)

Language barriers within the Winnipeg regional health authority. Evidence and implications - Bowen, Sarah (Winnipeg Regional Health Authority, 2004)

Évaluation de l’offre active des services de santé de première ligne - Comité santé en français de Fredericton (Groupe Progecom communication et stratégies d’entreprise, 2006)

Les minorités prennent la parole : résultats de l'Enquête sur la vitalité des minorités de langue officielle - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistique Canada, 2007)

Minorities speak up: Results of the survey on the vitality ot the Official-Language Minorities - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistics Canada, 2007)

Utilisation des services gouvernementaux de langue française. Une étude auprès des Acadiens et francophones de la Nouvelle-Écosse sur les facteurs associés à l’utilisation des services gouvernementaux en français - Deveau, Kenneth; Landry, Rodrigue; Allard, Réal (Institut canadien de recherche sur les minorités linguistiques, 2009)

Liminaire: Les enjeux reliés à la santé des communautés francophones en situation minoritaire - Forgues, Éric; Guignard Noël, Josée; Landry, Rodrigue (Francophonies d’Amérique, 2009)

La contribution des centres scolaires communautaires à la santé des francophones vivant en milieu minoritaire - Harrison, Suzanne (Francophonies d'Amérique, 2009)
La santé des francophones vivant en milieu minoritaire est un sujet d’actualité. Récemment, les centres scolaires communautaires (CSC) ont commencé à explorer leur contribution en cette matière, puisque traditionnellement, leurs activités portaient sur les besoins culturels, éducatifs et sociaux des francophones. Cet article présente les résultats d’une étude qui examinait la capacité des CSC à augmenter le contact avec la langue française dans huit domaines de vie. Les centres ne semblent pas encore contribuer à l’augmentation des contacts avec la langue française dans le domaine de la santé. Toutefois, des exemples révèlent qu’ils peuvent influencer, entre autres, la santé physique (cours d’aérobie, sports collectifs) et psychologique (cours sur la gestion du stress).

Communicative sensitivity in the bilingual healthcare setting: A qualitative study of language awareness - Irvine, Fiona. E.; Roberts, Gwerfyl. W.; Jones, Peter; Spencer, Llinos. H.; Baker, Colin. R.; Williams, Cen (Journal of Advanced Nursing, 2006)
Aim. This paper reports on the second phase of a national study in Wales. The research aimed to assess the level of Welsh language awareness amongst healthcare professionals across Wales, and to identify the factors that enhance language choice within service delivery. Background. The literature suggests that language sensitive healthcare practice is central to ensuring high quality care. However, it is evident that language barriers continue to compromise the quality of care within nursing and other health services. One issue that has received little attention is the level of language awareness that healthcare professionals currently demonstrate. Furthermore the factors that influence language choice for bilingual/multilingual speakers are not well explored in the literature. Methods. The study involved semi-structured interviews with a range of healthcare professionals in acute and community settings across Wales. Using a systematic sampling matrix, a purposeful sample of 83 professionals was selected to participate. Twenty-seven of the respondents were nurses, health visitors and midwives. The interviews focussed on the factors that facilitate or impede language sensitive healthcare practice. All interviews were audiotaped and, using a framework analysis approach, conceptual codes were developed and defined and categories and sub-categories were constructed to create thematic charts. Findings. Three main themes were identified: care enhancement, which focussed on the process and outcome of offering language choice to bilingual patients; organizational issues, which reflected issues relating to the infrastructure of service provision; and training implications, which focused on Welsh language learning in health care. Conclusions. Complex dynamics of language use are in operation within bilingual healthcare settings and organizational as well as individual factors are important in facilitating appropriate language use. Many of the issues highlighted are not peculiar to the Welsh context, but apply to healthcare settings across the world, where other minority languages are in use.

La littérat'ie en santé et les communautés francophones, minoritaires et ethnoculturelles - Kaszap, M.; Zanchetta, M. S. (Lire le monde : les littératies multiples et l'éducation dans les communautés francophones, 2009)

Les services de santé au Canada : une perspective linguistique - Lacroix, Frédéric (L'Action nationale, 2006)

Accès aux services de santé et aux services sociaux en anglais au Québec. Rapport de données de base 2005-2006 - Pocock, Joanne (Réseau communautaire de santé et de services sociaux, 2006)

Des services de santé en français dans un Nord en mutation. Un défi intercommunautaire - Réseau Santé en français au Nunavut (Association des Francophones du Nunavut, Santé en français au Nunavut, 2006)

Quand la langue fait une différence. Ce que des « bénéficiaires » pensent du système de santé mentale - St-Amand, Nérée; Vuong, Dung (Sociologie et sociétés, 2002)
Résumé En partant d'une recherche effectuée en 1993 auprès d'une soixantaine d'ex-psychiatrisés néo-brunswickois qui fréquentent maintenant des réseaux d'entraide de cette province, cet article met en évidence certains des enjeux auxquels sont confrontées les personnes " trans-institutionnalisées ". Il en ressort plusieurs différences au niveau de l'utilisation des services et du degré de satisfaction, selon l'appartenance sexuelle et la langue en particulier. De plus, cette recherche démontre que le réseau sur lequel s'appuient les ex-psychiatrisés francophones interrogés est davantage social (familles, groupe d'entraide), alors que pour la population anglophone, l'appareil institutionnel (psychiatres, institutions et cliniques) joue un rôle déterminant. Ceci soulève plusieurs questions, tant au niveau des politiques sociales que des pratiques d'intervention, en contexte minoritaire en particulier. Abstract On the basis of research carried out in 1993 on sixty or so ex-psychiatric patients who now frequent mutual aid networks in New Brunswick, this paper points out some of the issues with which these 'trans-institutionalized' persons are confronted. Differences at the level of service use and degree of satisfaction stand out, particularly in relation to gender and language. Moreover, this research shows that the network on which Francophone ex-psychiatric patients depend is more social in nature (families, mutual aid groups), whereas for the Anglophone population the institutional apparatus (psychiatrists, institutions and clinics) play a determining role. This brings up several questions, in regards to social policies as well of intervention practices, particularly in the minority context. Resumen Partiendo de una investigación efectuada en 1993 sobre unos sesenta ex-pacientes psiquiátricos de Nueva Brunswick que frecuentan actualmente la red de ayuda mutua de esta provincia, este articulo pone en evidencia algunas de las disyuntivas a las cuales se ven confrontadas las personas " trans-institucionalizadas ". Resaltan varias diferencias a nivel de la utilización de servicios y del grado de satisfacción, particularmente según la pertenencia sexual y el idioma. Además, esta investigación demuestra que la red sobre la cual se apoyan los ex-pacientes psiquiátricos francófonos interrogados, es mucho más social ( familia, grupo de ayuda mutua) mientras que para la población anglófona, el aparato institucional (psiquiatras, instituciones y clínicas) juega un rol determinante. Esto sugiere varias preguntas, tanto a nivel de las políticas sociales como de las prácticas de intervención, particularmente en un contexto minoritario.

Culture, language and self- assesments of future health: Anglophones and Francophones in Quebec’s Eastern Townships - Stout, Dale; Charpentier, Claude; Chiasson, Myriam; Filion, Emmalie (Journal of Eastern Townships Studies, 2009)
This study examines subjective ratings of health (SRH) by Francophones and Anglophones living in the Eastern Townships. Global self-ratings of health are regarded as sensitive predictors of future health states, mortality, functional decline and disability, and utilization of the health-care system. Yet despite their pragmatic value, SRH are poorly understood. Along with a spontaneous monitoring of present health states, culture and language are listed as determinants of SRH. Few studies exist, however, that clearly delineate the direction and degree of effect that culture and language have on SRH. Adopting a temporal assessment of SRH, we asked 358 Anglophones (N=176) and Francophones (N=171) from the Eastern Townships, aged 18 to 95, to rate their health in the past, present, and future. To isolate culture and language effects we also asked participants to rate their future health if they “remained in Quebec”. Results revealed a significant interaction between age and temporal ratings of health (SRH). Turning to the effects of location (unspecified or “in Quebec”) on future health ratings, there was a significant interaction with language. Post hoc tests revealed no significant differences in Francophones’ future health ratings (unspecified or “in Quebec”) but a significant ratings drop was noted for Anglophones if they “remained in Quebec”. After controlling for bilingualism, this interaction remained statistically significant.

The effects of age and culture on subjective well-being: A case study in the Eastern Townships - Stout, Dale; Filion, Emmalie; Chiasson, Myriam; de Man, Anton; Charpentier, Claude; Pope, Megan (Journal of Eastern Townships Studies, 2008)
The present study of diachronous ratings of subjective well-being (SWB) was modeled on research undertaken by Staudinger, Bluck & Herzberg (2003). In addition, we were interested in determining the effects of culture and context (where one lives) on SWB ratings. To gage these effects, we included the factor of mother tongue and altered the Life Satisfaction Questionnaire by adding a question concerning expected well-being in Quebec. We asked 350 Anglophones and Francophones from the Eastern Townships, aged 18 to 95, to rate their SWB in the past, present, future, and future ‘in Quebec’. The results concerning the effects of chronological age on diachronistic SWB ratings followed the patterns of previous research: young people (aged 18–38) rate past SWB lower than present SWB and future SWB much higher; middle-aged people (aged 39–64) rate their SWB the same regardless of time; And the elderly (67–95) rated past SWB higher than the present and their future SWB much lower. There were no differences between Anglophones or Francophones. Further analysis revealed the disturbing finding that the oldest participants rated their current SWB significantly lower than the other two age groups. In the second half of our study we found that by simply asking Francophones and Anglophones to rate their SWB in the future – first unspecified as to location, and then in a future ‘if they stay in Quebec’ – produced different response patterns. Both future SWB ratings were the same for Francophones, indicating that the questions were simply redundant. The Anglophones, on the other hand, rated their future SWB in Quebec consistently lower than an unspecified future.